2004
DOI: 10.1111/j.1467-8624.2004.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Interdependence and Academic Adjustment in College: Youth From Immigrant and U.S.‐Born Families

Abstract: This study is an examination of family interdependence and its implications for academic adjustment among late adolescents and young adults in college (18 to 25 years). Survey data and university records were collected on 998 American youth with Asian Pacific, Latino, African/Afro-Caribbean, and European backgrounds. Results indicate that Asian Pacific Americans placed more importance on family interdependence than did European Americans. Across all panethnic groups, youth with immigrant parents placed greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
215
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(236 citation statements)
references
References 35 publications
(40 reference statements)
15
215
6
Order By: Relevance
“…One major source of their motivation derives from their values of family obligation, their sense to support, respect, and help their family (Fuligni 2001;Tseng 2004). Nevertheless, we found that the school achievement of students from Mexican and Chinese backgrounds may suffer when family assistance is a chronic activity that occurs across many days of the week.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…One major source of their motivation derives from their values of family obligation, their sense to support, respect, and help their family (Fuligni 2001;Tseng 2004). Nevertheless, we found that the school achievement of students from Mexican and Chinese backgrounds may suffer when family assistance is a chronic activity that occurs across many days of the week.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, ethnographic work has shown that adolescents from immigrant families often report a sense of conflict and feel torn between doing their school work and assisting their family (Suarez-Orozco and Suarez-Orozco 1995;Suarez-Orozco 1991). Further, immigrant college students who assist their family more receive lower grades despite their increased academic motivation (Tseng 2004). In addition, young adults who provide financial support to their family are less likely to pursue postsecondary school, and those who live with their parents receive lower grades (Fuligni and Witkow 2004).…”
Section: Family Assistance and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in the present study we examined whether trajectory groups varied across positive youth domains related to confidence, competence, and connection (Lerner, 2004): self-esteem, general self-efficacy, academic self-efficacy, GPA, and family cohesion (Fuligni, Tseng, & Lam, 1999;Qin, 2006;Tseng, 2004).…”
Section: Associations With Positive Youth Developmentmentioning
confidence: 99%
“…Drawing on Bronfenbrenner's ecological theory (1986), we propose a conceptual ecological model of AA adolescent-parent relationships to identify factors that affect AA adolescent-parent relationships and position them within a set of nested domains representing has been suggested, however, that family interactions might be particularly important for adolescents from a cultural background that emphasizes family interdependence as is the case with Asian Americans (e.g., Tseng, 2004). We will focus on parenting and parent-child dynamics in AA families as they play an important role in adolescents' experiences in their relationship with their parents, and are often the focus of the existing literature on parentadolescent relationships in these families.…”
Section: Ecological Model Of Asian American Adolescent-parent Relatiomentioning
confidence: 99%